Pengaruh Pengembangan Sumber Daya Manusia, Budaya Organisasi dan Motivasi terhadap Kinerja Karyawan PT. Pertamina (Persero) Unit Pengolahan V Balikpapan - Kalimantan Timur - Fariansyah Hassan Basrie (BISMA (Bisnis dan Manajemen), 2018)
This research aimed to analyzis effect of: 1) human resource development, corporate culture, motivation toward employee performance, 2) corporate culture toward human resource dvelopment, 3) corporate culture toward motivation, 4) motivation toward human resource development and, 5) human resource development toward motivation in PT Pertamina (Persero) Processing Unit V East Kalimantan.Furthermore, object of this research was PT Pertamina (Persero) Processing Unit V East Kalimantan. This study using survei method with cross section analyzis. Sample using purposive sampling method. Respondance of this research was 16332 fixed, 1599 unfixed employee of PT Pertamina (Persero) Processing Unit V East Kalimantan. Each of population take as respondance 95 employee, total respondance 190. Sum of, 174 respondace take a questioner bac (almost 92%) model testing using structural equation modelling.In addition, this research found that corporate cuturw was build with increased inovation culture, organization activity base on employee orientation, and take attention to any problem cause be employee bring implication and better relation was a side effect of corporate culture and give space for employee to inovation and it can accomodate existing problem.This research also proofing that developing education and training, working capacity, knowladge ability, skill ability and on the job training, it can reach corporate objective. This research show that motivation had negative influence toward human resource development.This result also give information, that corporate culture had not directed effect on wok performance. On the other hand, other variable was give splilover effect. It was work motivation. This variable can be organization effort within increasing employee performance and organization.